Contemporary Literature Genre in the 21st Century: Basis for Pedagogical Teaching and Writing - Mallillin, Leovigildo Lito D. (PUSAKA: Journal of Educational Review, 2024)
The study aims to navigate contemporary literature genres in the 21st century as a basis for pedagogical teaching and writing. Mixed methods and purposive sampling are utilized in selecting the study's sample to obtain fifty (50) respondents. Results show that contemporary literature genre in the 21st century as a basis for pedagogical teaching and writing defines genre of fiction in every short story with no set of words on traditional flash stories, show that contemporary novel is written at present and discusses about the genre of life, show that poetry evokes on the response of the language through chosen rhythm, sound, and meaning, show that flash creates and provides incisive dense prose and intensity of poetry and accessibility among the modern readers, show that short story focuses on the different plot of elements, story structure, pacing, and character, show that slam poetry is competitive poets and art forms in experienced or aspiring performance opportunity engaged in live audience and reactions, show that play is a literary type of work that designs the stage performance in front of the audience or theater, and show that memoirs provide factual stories about someone’s life that reminisce the past experiences to the fullest.